2013
DOI: 10.1007/s11046-013-9620-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Methods in the Evaluation of Onychomycosis

Abstract: Onychomycosis is a common nail problem, accounting for up to half of all nail diseases. Several nail disorders may mimic the onychomycosis clinically. Therefore, a sensitive, quick, and inexpensive test is essential for screening nail specimens for the administration of the proper drug. The aim of this study was to compare 4 different diagnostic methods in the evaluation of onychomycosis and to determine their sensitivity, specificity, positive predictive value, and negative predictive value. In a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 29 publications
2
52
2
4
Order By: Relevance
“…Onychomycosis (plural: onychomycoses) is a common condition, making up approximately half of all nail disorders 1 . Dermatophytes have previously been reported to be the dominant aetiological agents in onychomycosis 1,2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onychomycosis (plural: onychomycoses) is a common condition, making up approximately half of all nail disorders 1 . Dermatophytes have previously been reported to be the dominant aetiological agents in onychomycosis 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Dermatophytes have previously been reported to be the dominant aetiological agents in onychomycosis 1,2 . All three dermatophyte genera (Trichophyton, Epidermophyton and Microsporum) are implicated in onychomycosis.…”
Section: Introductionmentioning
confidence: 99%
“…the high prevalence (99%) of onychomycosis in the trial by Haghani et al 14 The test statistics from Weinberg et al demonstrated in-clinic KOH sensitivity and specificity values of 80% and 72%, respectively, and PAS sensitivity and specificity values of 92% and 72%, respectively. Given the lack of data regarding the effect of KOH testing on sequential PAS testing, we assumed in our model that the performance of PAS was independent of KOH results.…”
mentioning
confidence: 95%
“…Models 2 and 3 were chosen based on multiple studies and international guidelines that recommend the use of PAS for out-of-office testing and in-clinic KOH screening as the least costly, most broadly available in-office procedure. 1,5,[11][12][13][14][15][16] Assigning Cost and Classification Probabilities…”
mentioning
confidence: 99%
See 1 more Smart Citation